Higher Objectives of Islamic Investment Products: Islamizing Indonesian Capital Market - Andri Soemitra (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2016)
Indonesian capital market regulators have already accommodated Islamic products as one of Indonesian capital market products. Theoretically, Islamic investment promises three main benefits i.e. spiritual, financial, and social benefits. Realizing Islamic investment in the sense of those three main benefits needs serious effort. This paper discusses the perception of capital market investors. This study suggests that their opinion as to whether or not sharī‘ah capital market products had fulfilled their expectations of Islamic comprehensive objectives. Islamic capital market instruments are part of Islamic instruments. The Islamization of financial institutions and instruments in the modern era has emerged not only to meet Muslims’ need for financial activities but also as the medium to realize the higher objectives of Islam, i.e. maqāṣid al-sharī‘ah in economic and financial activities.DOI: 10.15408/sdi.v23i2.2408